Compressed Sensing–Sensitivity Encoding (CS-SENSE) Accelerated Brain Imaging: Reduced Scan Time without Reduced Image Quality - Vranic, J.E.; Cross, N.M.; Wang, Y.; Hippe, D.S.; de Weerdt, E.; Mossa-Basha, M. (American Journal of Neuroradiology, 2019)
BACKGROUND AND PURPOSE: Compressed sensing–sensitivity encoding is a promising MR imaging acceleration technique. This study compares the image quality of compressed sensing–sensitivity encoding accelerated imaging with conventional MR imaging sequences.MATERIALS AND METHODS: Patients with known, treated, or suspected brain tumors underwent compressed sensing–sensitivity encoding accelerated 3D T1-echo-spoiled gradient echo or 3D T2-FLAIR sequences in addition to the corresponding conventional acquisition as part of their clinical brain MR imaging. Two neuroradiologists blinded to sequence and patient information independently evaluated both the accelerated and corresponding conventional acquisitions. The sequences were evaluated on 4- or 5-point Likert scales for overall image quality, SNR, extent/severity of artifacts, and gray-white junction and lesion boundary sharpness. SNR and contrast-to-noise ratio values were compared.RESULTS: Sixty-six patients were included in the study. For T1-echo-spoiled gradient echo, image quality in all 5 metrics was slightly better for compressed sensing–sensitivity encoding than conventional images on average, though it was not statistically significant, and the lower bounds of the 95% confidence intervals indicated that compressed sensing–sensitivity encoding image quality was within 10% of conventional imaging. For T2-FLAIR, image quality of the compressed sensing–sensitivity encoding images was within 10% of the conventional images on average for 3 of 5 metrics. The compressed sensing–sensitivity encoding images had somewhat more artifacts (P = .068) and less gray-white matter sharpness (P = .36) than the conventional images, though neither difference was significant. There was no significant difference in the SNR and contrast-to-noise ratio. There was 25% and 35% scan-time reduction with compressed sensing–sensitivity encoding for FLAIR and echo-spoiled gradient echo sequences, respectively.CONCLUSIONS: Compressed sensing–sensitivity encoding accelerated 3D T1-echo-spoiled gradient echo and T2-FLAIR sequences of the brain show image quality similar to that of standard acquisitions with reduced scan time. Compressed sensing–sensitivity encoding may reduce scan time without sacrificing image quality.CNRcontrast-to-noise ratioCScompressed sensingSENSEsensitivity encodingSPGRecho-spoiled gradient echo